Proteomic profiling of cotton fiber developmental transition from cell elongation to secondary wall deposition - Zhou Xiaoyun; Hu Wenran; Li Bo; Yang Yang; Zhang Yong; Thow Kieran; Fan Ling; Qu Yanying (Acta Biochimica et Biophysica Sinica)
Abstract Cotton fiber developmental transition from elongation to secondary cell wall biosynthesis is a critical growth shifting phase that affects fiber final length, strength, and other properties. Morphological dynamic analysis indicated an asynchronous fiber developmental pattern between two most important commercial cotton species, Gossypium hirsutum (Gh) and G. barbadense (Gb). Using isobaric tags for relative and absolute quantitation techniques, we examined the temporal changes of protein expression at three representative development periods (15–19, 19–23, and 23–27 dpa) in both species. Strikingly, a large proportion of differentially expressed proteins (DEPs) were identified at 19–23 dpa in Gh and at 23–27 dpa in Gb, corresponding to their fiber developmental transition timing. To better understand fiber transitional development, we comparatively analyzed those DEPs in 19–23 dpa of Gh vs. in 23–27 dpa of Gb, and noted that these cotton species indeed share fundamentally similar fiber developmental features under the biological processes. We also showed that there are limited overlaps in both specific upregulated and downregulated proteins between the two species, suggesting species-specific protein regulations in the development process. Proteomic profiling results revealed dynamic changes of several key proteins and biological processes that are potentially correlated with fiber developmental transition. During the transition, upregulated proteins are mainly involved in carbohydrate/energy metabolism, oxidation–reduction, cytoskeleton, protein turnover, Ca2+ signaling, etc., whereas important downregulated proteins are mostly involved in phenylpropanoid and flavonoid secondary metabolism pathways. The gene expressions of several changed proteins in this key stage were also examined by quantitative reverse transcription polymerase chain reaction. Overall, the present study provides accurate pictures of the regulatory networks of functional proteins during the fiber developmental transition, therefore highlighting candidate genes/proteins and related pathways for the cotton fiber improvement.